Keuangan digital: suatu studi literatur - Artha, Bhenu; Sari, Utami Tunjung; Sari, Niken Permata; Khairi, Ardhi; Bahri; Suhartini, Tien (Universitas Widya Mataram, 2023)
The financial industry has experienced a continuous evolution in service delivery due to digitization, where this evolution is characterized by expanded connectivity and improved information processing speed both at the customer interface and in back-office processes. The role of contracts in the economy has recently received great attention, where contracts are an important element of the operation of a market economy. The relevance of digital finance and financial inclusion for poverty alleviation and economic growth is of interest to policymakers and academics alike, particularly because of a number of issues that if addressed can make digital finance work better for individuals, businesses, governments and economies. Digital finance and financial inclusion have several benefits for financial service users, digital financial providers, governments and the economy such as increasing financial access among poor individuals, reducing financial intermediation costs for banks and fintech providers, and increasing aggregate spending for governments. The purpose of this study was to determine the determinants of digital finance. This study used a systematic literature review method and used 18 articles as study material, which were obtained from the scopus.com and sciencedirect.com pages. The results of the study show the determinants of digital finance, both variables that influence, are influenced or mediate. The results of the literature study did not find digital finance as a moderating variable.